Closing the gender gap: Panel discussion - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Panel discussion at the Closing the gender gap in farming under climate change event held 19 March 2015 in Paris. Mary Robinson, President, Mary Robinson Foundation - Climate Justice Sir Gordon Conway, Director of Agriculture for Impact and Professor of International Development at Imperial College London. Ann Tutwiler, Director General, Bioversity International Jane Madgwick, CEO, Wetlands International Dr. Evelyn Namubiru-Mwaura, Policy Officer, Alliance for a Green Revolution in Africa (AGRA) Moderator: Heide Hackmann, Executive Director, International Council for Science (ICSU) Welcome by Frank Rijsberman, CEO, CGIAR Consortium Read more about the event: https://ccafs.cgiar.org/events/closing-gender-gap-farming-under-climate-change-new-knowledge-renewed-action